The role of viruses in the development of cancer (2024)
Cancer continues to be a leading cause of death globally. According to the World Health Organisation, it ranked second most common cause of death globally, claiming millions of lives with millions of new cases diagnosed yearly. Despite recent advances in cancer research and availability of several therapies, severe adverse effects, multi-drug resistance and cost of management are drawbacks of available therapies. Hence, the need for novel approaches that will mitigate the limitations of these conventional treatment options. Cancer has been linked to several factors and while the focus is usually on carcinogenic substances, viruses have been found to account for 15-20% of cancer cases. Oncolytic viruses are viruses that are used in cancer treatment. These viruses have the ability to selectively infect and replicate within tumor cells making them specific in their action against them. This promising approach is also effective when combined with other cancer treatment options such as chemotherapy and radiation.